Memories of Siberian Pilgrims on Palestine of Late 19th - Early 20th Century as Historical Source - A. A. Valitov; T. A. Kibardina (Научный диалог)
Memories of Siberian pilgrims of the late 19th - early 20th century are considered as a historical source. The intensification of pilgrimages to the main Christian shrines of the inhabitants of the Russian Empire during this period is naturally associated with the emergence and activities of the Imperial Orthodox Palestinian Society (IOPS). Regional departments of the society appeared in Siberia (Tobolsk, Tomsk, Yenisei, Chita and Yakut departments). The authors note that thanks to the activities of local departments of the IOPS, the broad strata of the inhabitants of the Empire at the turn of the 19th - early 20th centuries were able to make pilgrimages to the Holy Land. It is reported that the written memories of Siberian pilgrims who made multi-day trips to the main shrines of the Middle East have been preserved. The study of these materials allows to conclude that the records were mainly kept by the clergy, some of them were published on the pages of the local diocesan press. The authors point out that the pilgrims, writing down their impressions and memories, paid special attention to the image of Palestine. It is indicated that part of the memories and personal experiences were used as an important source in the Palestinian readings conducted by the regional divisions of the IOPS. It is argued that the diary entries are an important historical source that allows readers to create a holistic image of Palestine.